Muscle strength evaluation of limb dominance in prepubescent swimmers boys and girls - Özcadirci, A.; Özturk, F.; Cinemre, S. A.; Kinikli, G. (Baltic Journal of Health and Physical Activity, 2021)
Background: The aim of this study was to compare the lower limb muscle strength in terms of gender and limb dominancy in prepubescent swimmers. Material and methods: Seventy-four prepubescent swimmers (mean age: 11.01±1.58 years; 42 boys; 32 girls) who were training for at least 8 hours a week and without current lower limb pain participated in the study. Isometric muscle strength of lower limb was measured by hand-held dynamometry. Independent samples-t test was used to determine the difference between genders, while paired samples-t test was used for dominant-nondominant side comparison. The significance level was accepted as p<0.05. Results: Knee flexion (p<0.001), extension (p<0.001) and ankle dorsiflexion (p=0.003) muscle strength were stronger on the dominant side than on the non-dominant side. Knee flexion/extension strength ratio was similar (p=0.957); while ankle plantar flexion/dorsiflexion strength ratio was significantly different (p=0.011). Boys swimmers had stronger isometric muscle strength in the dominant side together with knee flexion (p=0.018) and knee flexion extension strength ratio (p=0.007) than girls swimmers. Conclusions: Boys swimmers had higher dominant side knee flexion muscle strength compared to female peers. Gender and lower limb dominancy might be important for lower limb muscle strength to show varieties in prepubescent swimmers before planning a training program.